Transformational Leadership and Work Environment: Enhancing Job Satisfaction and Performance: Kepemimpinan Transformasional dan Lingkungan Kerja: Meningkatkan Kepuasan Kerja dan Kinerja - Andika Ridwana Putra; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative research study aims to examine the relationships between transformational leadership, work environment, job satisfaction, and employee performance in IKM Kampung Pia Gempol Pasuruan. Through a purposive sampling technique, data was collected from 85 employees using a questionnaire. The study employed path analysis and SPSS Statistics version 22 software for data analysis. The results indicate that transformational leadership and work environment have positive and significant effects on job satisfaction. Furthermore, transformational leadership and work environment positively influence employee performance. Job satisfaction is found to have a positive and significant impact on employee performance. Moreover, the study demonstrates that transformational leadership and work environment have direct and indirect effects on employee performance when job satisfaction acts as the mediating variable. These findings contribute to the understanding of the importance of leadership, work environment, and job satisfaction in enhancing employee performance. Practical implications are discussed, emphasizing the significance of fostering a transformational leadership style, improving the work environment, and promoting job satisfaction to maximize employee performance. Highlights: Transformational leadership and work environment positively influence job satisfaction and employee performance. Job satisfaction has a significant impact on employee performance. Transformational leadership and work environment have direct and indirect effects on employee performance, with job satisfaction as a mediating variable. Keywords: Transformational leadership, work environment, job satisfaction, employee performance, path analysis.